A study on the introduction of mixed payment compensation system through top-down cost information analysis in Korea - Kim, Han-sung; Woo, Jung-sik (Edelweiss Applied Science and Technology, 2024)
This study aims to identify the problems of the Korean health insurance fee system and to suggest a reasonable insurance fee construction alternative using the cost analysis data of hospitals. To this end, the characteristics of the medical fee payment system and hospital cost analysis were examined, and the cost data of one national public general hospital were used for the analysis. The cost allocation criteria were divided into labor costs, material costs, pharmaceutical costs, equipment costs, and overhead costs, and a top-down cost analysis was conducted. The analysis results showed that the cost was greater than the income in the case of outpatient and inpatient treatment performance, and the analysis results on the amount of physician workload showed that the relative value of physician workload calculated based on the cost was analyzed to require an increase of 1.52 times for hospitalization fees and 1.72 times for examination fees. The main factor affecting the cost compensation rate was that when the proportion of examination fees was high, the cost compensation level increased, while on the other hand, the cost compensation rate decreased as the proportion of physician labor costs increased or the length of stay increased. In order to resolve the ongoing complaints of medical service providers under the current fee-for-service system and secure the appropriateness of health insurance compensation rates, compensation for physician fees should be induced to realize the level of cost compensation through cost-based, per-service fee calculations, and the rationality of the payment compensation system can be secured by securing autonomy of providers through bundled fees for hospital costs and changing the payment method.